Targeting NF-κB/AP-2β signaling to enhance antitumor activity of cisplatin by melatonin in hepatocellular carcinoma cells - Hao, Jiaojiao (Am J Cancer Res, 2017)
Cisplatin is a common chemotherapeutic drug for cancer treatment, but its effect is limited because of its cytotoxicity and chemoresistance. The combinational use of cisplatin with some natural compounds has provided a potential option to improve its effect and lower its side effects in cancer treatment. Here, we investigated the role of melatonin in the regulation of cisplatin-mediated antitumor activity in hepatocellular carcinoma cells. The combined treatment of cisplatin with melatonin significantly inhibited cell proliferation and resulted in a corresponding decrease of the IC50 values of cisplatin in four hepatocellular carcinoma cell lines. Cotreatment with melatonin also increased the cisplatin-induced apoptosis in hepatocellular carcinoma cells compared with cisplatin treatment alone. Further mechanism studies showed that the combined treatment of melatonin and cisplatin enhanced the cleavage of caspase-3, caspase-9 and poly-(ADP-ribose) polymerase (PARP), decreased the expression of Bcl-2 and p-IKKα/β, suppressed the nuclear translocation of NF-κB p50/p65 proteins, and abrogated the binding of p65 to COX-2 promoter, thereby inhibiting COX-2 expression. Furthermore, melatonin was found to synergistically enhance cisplatin-mediated inhibition of AP-2β and hTERT expression. Overexpression of AP-2β reversely rescued this inhibition mediated by the combined treatment of these two drugs. Collectively, our results demonstrated that melatonin sensitizes the cisplatin-mediated growth suppression of cells via the inactivation of NF-κB/COX-2 and AP-2β/hTERT signaling in hepatocellular carcinoma cells.